El entierro múltiple de Cabo Dos Bahías (Patagonia Central Argentina): recuperación de información de la colección Frengüelli-Brunet - Millan, Ana Gabriela (2022)
The Cabo Dos Bahías burial was excavated in 1984 by Rodolfo Brunet, an archaeology collector from Puerto Madryn, Chubut province (Argentina). In this paper we present the results of archaeological, bioanthropological and taphonomic studies of the six individual recovered from that site. The obtained information allow us to interpret that it was a reused funerary space where six individuals were buried close to the shore circa 2000 years ago. The sample consists of five adults (four males and one female) and a subadult of undetermined sex. These individuals had a mixed terrestrial-marine diet, but with different emphasis on the proportion of high trophic level marine fauna. Their morphological characteristics and their stature indicate biological relationships with groups of hunter-gatherers from the coast of central Patagonia.